Multidisciplinary Management of Placenta Accreta Spectrum in a Rural Indonesian Hospital - Wim Pratama Wijaya; Agustinus Gusti; Michael Reiner Wangania; Firman Nugroho; Maya Permatasari Suyata (Indonesian Journal of Obstetrics and Gynecology, 2026)
ABSTRACT Objective: To describe the challenges of diagnosing and managing Placenta Accreta Spectrum (PAS) in a rural setting, particularly when referral to a specialized center is not feasible. Methods: Case report. We report a case of PAS managed in a resource-limited rural hospital at Siloam Hospitals Labuan Bajo, West Manggarai, Indonesia. Results: A 34-year-old multigravida with no antenatal care was diagnosed at 34 weeks’ gestation with placenta previa accreta and a singleton pregnancy. She had a history of one previous cesarean section and was admitted with antepartum hemorrhage. A planned referral to a specialized PAS center in Surabaya was interrupted by recurrent bleeding leading to hemorrhagic shock. An emergency cesarean section followed by hysterectomy was performed by a coordinated multidisciplinary team involving obstetrics-gynecology, surgery, urology, and anesthesiology–intensive care. The estimated blood loss was approximately 2000 mL. Both maternal and neonatal outcomes were favorable, with postoperative stabilization and no immediate complications. Histopathological confirmation was not performed due to limited facilities. Conclusion: Management of PAS in rural areas remains challenging because of limited access to early diagnosis, specialized referral centers, multidisciplinary teams, and blood bank services. This case highlights the importance of early recognition and multidisciplinary readiness to achieve favorable outcomes in low-resource settings. Keywords: antepartum hemorrhage, case report, multidisciplinary management, placenta accreta spectrum, rural settings